2007
DOI: 10.4049/jimmunol.178.5.2737
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Specific CD8+ T Cells in the Liver: Armed and Ready to Kill

Abstract: Influenza A virus infection of C57BL/6 mice is a well-characterized model for studying CD8+ T cell-mediated immunity. Analysis of primary and secondary responses showed that the liver is highly enriched for CD8+ T cells specific for the immunodominant H2DbNP366–374 (DbNP366) epitope. Functional analysis established that these liver-derived virus-specific CD8+ T cells are fully competent cytotoxic effectors and IFN-γ secretors. In addition, flow cytometric analysis of early apoptotic cells showed that these inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 78 publications
2
23
0
1
Order By: Relevance
“…Alternatively, the liver and the bone marrow are responsible for homeostatic expansion of nonoverlapping memory T cell subsets, or that renewed memory T cells from the liver and bone marrow may be functionally distinct. Reports contrasting the long-held view that the liver is a graveyard for activated T cells have been published (37)(38)(39). CD8 + memory T cells do more than gain entry and survive in the liver, our results show that they actually grow in the liver.…”
Section: Discussionsupporting
confidence: 52%
“…Alternatively, the liver and the bone marrow are responsible for homeostatic expansion of nonoverlapping memory T cell subsets, or that renewed memory T cells from the liver and bone marrow may be functionally distinct. Reports contrasting the long-held view that the liver is a graveyard for activated T cells have been published (37)(38)(39). CD8 + memory T cells do more than gain entry and survive in the liver, our results show that they actually grow in the liver.…”
Section: Discussionsupporting
confidence: 52%
“…The present study advances these findings by showing significant influenza-specific T cell accumulation at very early phases even before the systemic response is fully established, as well as the ability of these accumulating cells to exit the liver and to generate viable memory populations. This indicates an active role for the liver in contributing to mounting immune responses, which has been suggested (15) but not demonstrated.…”
mentioning
confidence: 97%
“…Keating et al (15) have concurrently found high viability among Ag-specific T cells in the liver at peak and resolution phases. Thus, mounting evidence indicates that during resolution, the liver does not merely harbor apoptosing T cells.…”
mentioning
confidence: 99%
“…24,25 Nevertheless, an increasing number of studies have demonstrated the presence of fully functional effector T cells in the liver. 26,27 Virus-specific T cells may be retained in the liver even though the virus is not known to infect this organ, and they can cause resulting bystander hepatitis even when hepatocytes do not express the antigen recognized by the T cells. [27][28][29] This was also evidenced in our study of HBsAg transgenic mice.…”
mentioning
confidence: 99%
“…26,27 Virus-specific T cells may be retained in the liver even though the virus is not known to infect this organ, and they can cause resulting bystander hepatitis even when hepatocytes do not express the antigen recognized by the T cells. [27][28][29] This was also evidenced in our study of HBsAg transgenic mice. First, the peripherally activated T cell response, which mostly comprised Flu-specific T cells but no HBsAg-specific T cells, may have partially reduced HBsAg production.…”
mentioning
confidence: 99%